Complete sequence of mitochondrial DNA of Gracilaria edulis (Rhodophyta). Issue 2 (2nd April 2020) - Sedanza, Mary Grace C.; Meinita, Maria Dyah Nur; Tang, Xianming; Chen, Weizhou; Yin, Hongxin; Liu, Cui; Jin, Yuemei; Chi, Shan; Li, Yue; Liu, Tao
Abstract: Herein, the complete Gracilaria edulis mitogenome was determined and analysed. The complete G. edulis mitogenome length was 25, 708 bp. The mitogenome contains 50 genes, including 24 protein-coding, two rRNA, and 23 tRNA genes and one unidentified open reading frame (ORF). Of the 24 protein-coding genes, 23 (95.83%) ended with the TAA stop codon, and one (4.17%) with TAG ( rpl 20). All protein-coding genes in G. edulis were concluded to use the start codon ATG. Mitogenome phylogenetic analysis revealed that G. edulis clustered together with G. changii and G. salicornia . The complete mitogenome sequence provided herein would help understand Gracilaria evolution.